2011
DOI: 10.1007/s00068-011-0139-9
|View full text |Cite
|
Sign up to set email alerts
|

What are the predictors of scapula fractures in high-impact blunt trauma patients and why do we miss them in the emergency department?

Abstract: After matching for ISS, the mortality of patients with scapula fracture was significantly higher than the control group. We observed that fractures in the glenoid and scapular neck occurred higher than in the body region. We found that the seniority of the ED doctor, consultation ratio for orthopedics in ED, and the existence of brain contusion were important parameters for missing scapula fractures in ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In severely injured patients, severe thoracic trauma increases the morbidity and mortality especially due to the increased risk of developing an acute respiratory distress syndrome (ARDS) [ 3 , 37 , 38 ]. Previous studies showed that up to 23.5% of thoracic injuries and 35.7% of scapula fractures are initially overlooked [ 4 , 15 ]. Therefore, thoracic injuries should always be considered in the occurrence of shoulder injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In severely injured patients, severe thoracic trauma increases the morbidity and mortality especially due to the increased risk of developing an acute respiratory distress syndrome (ARDS) [ 3 , 37 , 38 ]. Previous studies showed that up to 23.5% of thoracic injuries and 35.7% of scapula fractures are initially overlooked [ 4 , 15 ]. Therefore, thoracic injuries should always be considered in the occurrence of shoulder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In the present literature, several studies highlight the relevance of scapular fractures in a severe trauma or shoulder injuries in general [11][12][13][14][15]. Nevertheless, there are no studies of the TraumaRegister DGU® or similar international databases available that provide a complete overview of injuries of the shoulder in severe multiple trauma and their association with outcome, trauma mechanisms, or concomitant injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Scapular fractures in adults are usually the result of a direct blow and are often associated with clavicular or rib fractures [113]. Nowadays, scapular fractures mostly occur in motor vehicle accidents, falls from a height and assaults [119]. Bilateral fractures of the body have also been reported in epileptic seizures and electrocution [120].…”
Section: Discussionmentioning
confidence: 99%
“…However, he did not mention bilateral fractures. Outstanding in this respect is the study by Uzkeser et al [24]. In a group of 1,039 patients with high-impact blunt trauma, these authors recorded a scapular fracture in 42 cases (4 %), of which 25 % were overlooked on CT scans.…”
Section: Discussion and Literature Overviewmentioning
confidence: 99%
“…The prognostic relevance of scapular fractures in polytraumatised patients is the subject of widespread debate [23,24,27]. Some authors state that polytraumatised patients with a scapular fracture have more severe injuries and higher mortality rates, whereas other authors claim that such patients have more severe injuries to the chest but a lower mortality rate.…”
Section: Discussion and Literature Overviewmentioning
confidence: 99%